Determinantes de la violencia familiar contra las mujeres en el Perú: una estimación econométrica - León Mendoza, Juan (2011)
This article aims at fundamental to analyze the problem of physical, psychological and sexual violence against women by their spouses. With the aid of a microeconomic model formulated and using the information from ENDES 2009, the results of logistical regression econometric show that the main underlying variables that determine the probability of generating actions of spousal violence against women in Peru are: (a) that the woman is unemployed or not immersed in the labor market, (b) she has been physically assaulted by their parents during infancy or childhood, and (c) she is in a situation of married or conviviality.